The Characterisctic And Causes Of Josephine's Deviant Behaviors Reflected In Agatha Christie's Crooked House Novel(1949): A Psychoanalytic Approach - Rokama, Endang; , Dr.Phil Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.Si. M.Hum (2013)
The research investigates how the major character occurs to get causes of Josephine's deviant behaviors in Agatha Christie's Crooked House Novel. The study analyzes the novel in terms of it's structural elements and based on the psychoanalytic approach. The object of the study is the personality of the major character of Josephine. The data sources are literary data. Those are divided in two categories, primary data sources and secondary data some to are books and other sources which support the researcher in analyzing this research. The method of data collection of the study is library research. The technique of data analysis is descriptive analysis. Based on the analysis, the researcher draws two conclusions: first, based on the structural analysis of the novel, it has an important role to build up the story so each element. Second, the study shows that the cause deviant behaviors can change the personality. It is reflected in the major character's personality when she wants to kill her grandfather and Nannie.